1996
DOI: 10.1002/j.2164-4683.1996.tb00350.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Self‐Concept and Achievement for African American Preadolescents

Abstract: This study examined the relationship between 7 dimensions of self‐concept and achievement in 563 African American 4th‐, 5th‐, and 6th‐graders. After controlling for socioeconomic status, social self‐concept accounted for a significant amount of variability in achievement test scores, whereas school‐related self‐concepts did not. Results do not support earlier research on the relationship between self‐concept and achievement for African American students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 27 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…al. [28] conducted a study on African American elementary students (N= 563) and found no correlation between school related self-concept and achievement test scores. Similarly, Areepatiamannil and Freeman [29] found moderate correlation between academic self-concept and achievement of secondary school students.…”
Section: Studies On Academic Self Concept and Academic Achievementmentioning
confidence: 99%
“…al. [28] conducted a study on African American elementary students (N= 563) and found no correlation between school related self-concept and achievement test scores. Similarly, Areepatiamannil and Freeman [29] found moderate correlation between academic self-concept and achievement of secondary school students.…”
Section: Studies On Academic Self Concept and Academic Achievementmentioning
confidence: 99%
“…Dambudzo (2005) however, concluded that sports and academic achievement appear to have a mutual influence on each other. Trusty et al (1996) came to the conclusion that there is a negative relationship between social self-concept and academic achievement. Muijs (1997) concluded that academic selfconcept and academic achievement were best predictors of one another.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast with racial comparison studies, within-ethnic-group investigations of the multidimensional self-concept are rare (Crain & Bracken, 1994). One exception is a study that examined the relationship between the multidimensional self-concept and academic achievement of African American seventh and eighth graders (Trusty, Watts, & Lim, 1995). The strongest predictor of SAT scores (i.e., academic achievement) for this sample was social confidence, a measure of social self-efficacy or the degree to which the adolescent believes that others value his or her friendship.…”
Section: The Multidimensional Self-concepts Of African American Adolescentsmentioning
confidence: 99%